PENGARUH PERCEIVED USEFULNESS TERHADAP BEHAVIOR INTENTION TO USE E-WALLET GOPAY MELALUI MEDIASI ATTITUDE TOWARD USING DI KOTA TERNATE - Christina Yanita Setyawati; Desiree Clarissa Polar (Jurnal Akuntansi dan Pajak, 2022)
Gojek is a business startup that provides application-based services and has earned a Decacorn degree. Decacorn title can be awarded to business startups that have a valuation of above US $ 10 billion. The mobile payment facility, Gopay, is one of 20 services provided by Gojek to answer the needs of people who are starting to switch from using cash to mobile payment. One's interest in using a technology is influenced by several factors. In the Technology Acceptance Model (TAM) theory, there are several factors that influence the interest in using E-Wallet, namely perceived usefulness, attitude toward using, and behavioral intention to use. The purpose of this study was to determine the effect of perceived usefulness on behavioral intention to use e-wallet, Gopay, through mediating attitude toward using in Ternate City. The method in this research is descriptive quantitative, with analysis tools using partial least square. This study has a sample of 145 respondents. The results of the study showed that perceived usefulness influenced positively and significantly on behavioral intention to use, and attitude toward using. Attitude toward using influenced positively and significantly on behavioral intention to use. Perceived usefulness has a positive and significant effect on behavioral intention to use through attitude toward using as a mediating variable. Keywords: attitude toward using, behavioral intention to use, perceived usefulness, Technology Acceptance Model (TAM)